2020
DOI: 10.3390/coatings10060586
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrochemical Oxidation Behaviors and Mechanism of Single-Crystal Silicon (100) Wafer under Potentiostatic Mode

Abstract: Electrochemical oxidation (ECO) has been used widely to oxidize single crystal Si wafers. Aiming at optimizing the ECO assisted machining methods, the oxidation behaviors of single- crystal silicon (100) wafer under potentiostatic mode are experimentally investigated. It is shown that the Si wafer can be electrochemically oxidized and the oxidized film thickness reaches to 239.6 nanometers in 20 min. The hardness of the oxidized surface is reduced by more than 50 percent of the original surface. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Table 6 and Figure 7 show the acquired energy dispersive spectroscopy (EDS) analysis results of workpiece surfaces in Figure 6. As can be concluded from Table 6 and Figure 7, both the oxidation and element transfer effects occurred when processing the SiCp/Al composite in WEDM [55][56][57][58]. It can be found that oxygen atoms generally take more account of the workpiece surface processed by BWE than those processed by ZCSMWE by enforcing the same processing parameters.…”
Section: Workpiece Surface Topographymentioning
confidence: 80%
“…Table 6 and Figure 7 show the acquired energy dispersive spectroscopy (EDS) analysis results of workpiece surfaces in Figure 6. As can be concluded from Table 6 and Figure 7, both the oxidation and element transfer effects occurred when processing the SiCp/Al composite in WEDM [55][56][57][58]. It can be found that oxygen atoms generally take more account of the workpiece surface processed by BWE than those processed by ZCSMWE by enforcing the same processing parameters.…”
Section: Workpiece Surface Topographymentioning
confidence: 80%
“…In particular, it is irreversible under the thereby employed electrochemical conditions. Moreover, we did not apply higher voltages, as the resulting formation of thick oxide layers (beyond 10 nm) [ 48,51 ] would have resulted in a complete oxidation of the pore walls and thus in a nonconductive porous layer. Hence, a capacitive charging of the nanopores would have been impossible.…”
Section: Resultsmentioning
confidence: 99%
“…While most previous investigations used galvanostatic anodization of Si (where the current density remains constant), the application of the potentiostatic oxidation of silicon is still an open subject in the field [8,[14][15][16][17]. Actually, notwithstanding the undoubted importance of electrical potential in controlling the properties of PSi, electrochemical oxidation of silicon has mainly been carried galvanostatically, as opposed to potentiostatically, because of the difficulty of working with reference electrodes in HF solutions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up the process to industry standard of 200 mm diameter wafers does not foresee any fabrication challenges. Aside from the well-established galvanostatic anodization, potentiostatic anodization is gaining attention in structuring micro-/nanomaterials lately[17,19,[28][29][30][31], and this work can be used as a block in building advanced technologies.…”
mentioning
confidence: 99%